Multilayered Sporadic‐E Response to the Annular Solar Eclipse on June 21, 2020 - Jin Wang; Xiaomin Zuo; Yang‐Yi Sun; Tao Yu; Yungang Wang; Lihui Qiu; Tian Mao; XiangXiang Yan; Na Yang; Yifan qi; Jiuhou Lei; Lingfeng Sun; et al. (Space Weather)
Abstract A moon shadow of annular solar eclipse passed through East Asia in the afternoon on June 21, 2020, which was a good opportunity to study the rapid ionospheric response to the solar radiation variations. In the study, the high‐frequency echoes recorded by the ionosondes at Wuhan (82.4% obscuration), Xiamen (97.8% obscuration), and Nanning (81.1% obscuration) are analyzed to examine the variations in sporadic‐E (Es) during the obscuration over the East China area. The echoes show not only the variations in the typical signal Es layer below 130 km, but for the first time also the multilayered Es at much higher altitudes (130–190 km) during the eclipse. Specifically, the multilayered Es is only observed over Nanning, while different Es behaviors are observed in the other two stations. The relationship between the formation of the multilayered Es and the uplifted Es near the center path of the moon shadow are examined in the study. The small‐scale atmospheric gravity waves play a key role in modulating the Es behaviors during the eclipse.